1979
DOI: 10.1093/jn/109.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Control of Lipogenesis: Strain Differences in Hepatic Metabolism

Abstract: Detailed studies of hepatic metabolism of lipemic BHE and nonlipemic Wistar rats were conducted. Hepatic lipogenic capacity was varied through the use of starvation or meal feeding. Livers were clamped in precooled copper plates and used for the assay of glycolytic, gluconeogenic, and lipogenic metabolites. Redox and phosphorylation states were calculated. Mitochondrial metabolism was evaluated through studies of the oxygen consumption of isolated mitochondria and through the study of the activities of the alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The following studies involving BHE rats provide evidence for altered oxidative phosphorylation states, presence of mitochondrial retinoic acid receptors and hence the requirement for higher concentrations of vitamin A which also increases levels of mitochondrial transcription factor A (Berdanier et al 1979;Everts et al 2002). Mitochondrial metabolism was evaluated by measuring oxygen consumption of isolated mitochondria and by studying the activities of the alpha-glycerophosphate and malate aspartate shuttles and ATPase in lipemic BHE and nonlipemic Wistar rats (Berdanier et al 1979).…”
Section: Bhe Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following studies involving BHE rats provide evidence for altered oxidative phosphorylation states, presence of mitochondrial retinoic acid receptors and hence the requirement for higher concentrations of vitamin A which also increases levels of mitochondrial transcription factor A (Berdanier et al 1979;Everts et al 2002). Mitochondrial metabolism was evaluated by measuring oxygen consumption of isolated mitochondria and by studying the activities of the alpha-glycerophosphate and malate aspartate shuttles and ATPase in lipemic BHE and nonlipemic Wistar rats (Berdanier et al 1979).…”
Section: Bhe Ratsmentioning
confidence: 99%
“…The following studies involving BHE rats provide evidence for altered oxidative phosphorylation states, presence of mitochondrial retinoic acid receptors and hence the requirement for higher concentrations of vitamin A which also increases levels of mitochondrial transcription factor A (Berdanier et al 1979;Everts et al 2002). Mitochondrial metabolism was evaluated by measuring oxygen consumption of isolated mitochondria and by studying the activities of the alpha-glycerophosphate and malate aspartate shuttles and ATPase in lipemic BHE and nonlipemic Wistar rats (Berdanier et al 1979). Lipemic BHE rats had higher phosphorylation states, higher redox ratios, and lower shuttle activities and oxygen consumption by isolated mitochondria than their nonlipemic Wistar cohorts and the differences in oxidative phosphorylation, redox and phosphorylation states and in the various shuttle activities suggested that BHE liver cells were geared towards lipogenesis at the expense of oxidative phosphorylation.…”
Section: Bhe Ratsmentioning
confidence: 99%
“…Consequently, the efficiency of oxidative phosphorylation is compromised [3] and ATP production is reduced [4]. Previous studies established that aged male BHE/cdb rats had abnormal islet morphology, but relatively normal insulin content [5].…”
mentioning
confidence: 99%
“…Tolerance can be influenced by both age and diet. Gestational diabetes (glucose tolerance normal before and after gestation but not during the TABLE 1 Protocols Followed for the Development of the Cdb.BHE Rat Colony last third of gestation) can be shown in 200-day-old female rats if they are fed a 22 percent fat diet, which approximates the composition of the average diet consumed by people in the United States (Berdanier et al, 1979;Bue et al, 1989).…”
Section: Glucose Tolerancementioning
confidence: 99%
“…These values are only slightly higher than what one might anticipate for normal rats of this age. Fasting serum cholesterol values seem to be unaffected by diet composition, whereas, fasting serum triglycerides are elevated sometimes by as much as 50 percent when purified diets containing 5 percent saturated fat and/or 65 percent sucrose are fed (Berdanier et al, 1979;Kim et al, 1989). "Stock diet, Purina Laboratory Animal Chow.…”
Section: Blood Lipidsmentioning
confidence: 99%